The longmire defense eaudiobook - Johnson, Craig (Walt Longmire Mystery, 2023)
Sheriff Walt Longmire uncovers a cold case that hits very close to home and forces him to put his life on the line with implications that some people would kill to keep buried forever Sheriff Walt Longmire and Dog are called on a routine search and rescue to Wyoming's Bighorn Mountains, where Walt finds himself on a rock outcropping remembering when his father told him about the first time he saw a man die. In the late forties, Bill Sutherland was shot but the investigation was stymied because no member of the elk camp—where he was found—was carrying the caliber rifle that killed the state accountant. When Dog discovers the missing weapon, the sheriff of Absaroka County is plunged headfirst into a cold case. His investigation quickly finds ties to a hidden mineral fund that someone is willing to kill to keep secret. The embodiment of the fair-minded detective, Walt is pushed to his ethical boundaries. In his relentless pursuit of the truth, he discovers the rifle in question belonged to none other than Walt's infamous and uncompromising grandfather, Lloyd Longmire.